2019
DOI: 10.1097/dss.0000000000002229
|View full text |Cite
|
Sign up to set email alerts
|

Mohs Micrographic Surgery for the Treatment of External Ear Melanoma: an Outcome Study

Abstract: BACKGROUND The external ear is composed of thin skin overlying cartilage making melanoma on the external ear difficult to resect while preserving the intricate anatomy. Although surgeons have achieved robust clinical outcomes for nonmelanoma and most recently melanoma skin cancers with Mohs micrographic surgery (MMS), there is still not enough evidence on the MMS application for external ear melanoma treatment. OBJECTIVE The authors examined survival ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…At times, a particular location might lead to a consideration of Mohs surgery rather than traditional WLE to minimize skin loss. Examples include the eyelid [ 35 ], ear [ 36 ], lips [ 37 ], face [ 38 ], hands and feet [ 39 ]. In Australia, it has been concerning that many melanoma patients’ tumors are not excised with the required margins of clearance.…”
Section: Excision Marginsmentioning
confidence: 99%
“…At times, a particular location might lead to a consideration of Mohs surgery rather than traditional WLE to minimize skin loss. Examples include the eyelid [ 35 ], ear [ 36 ], lips [ 37 ], face [ 38 ], hands and feet [ 39 ]. In Australia, it has been concerning that many melanoma patients’ tumors are not excised with the required margins of clearance.…”
Section: Excision Marginsmentioning
confidence: 99%
“…demonstrated lower local recurrence rates for cutaneous head and neck melanoma after treatment with MMS (0.61%; 95% CI 0.1%–1.4%) vs. staged excision (1.8%; 95% CI 1.0%–2.9%) and WLE (7.8%; 95% CI 6.4%–9.3%). A study investigating excision of 8212 external ear melanomas 18 showed that survival after MMS was at least equivalent to that of WLE, but with the benefit of normal tissue preservation. Additionally, Terushkin et al 12 .…”
Section: Mohs Micrographic Surgery For Different Types Of Skin Cancermentioning
confidence: 99%
“…14 The meta-analysis published by Bittar et al 6 demonstrated lower local recurrence rates for cutaneous head and neck melanoma after treatment with MMS (0.61%; 95% CI 0.1%-1.4%) vs. staged excision (1.8%; 95% CI 1.0%-2.9%) and WLE (7.8%; 95% CI 6.4%-9.3%). A study investigating excision of 8212 external ear melanomas 18 showed that survival after MMS was at least equivalent to that of WLE, but with the benefit of normal tissue preservation. Additionally, Terushkin et al 12 found in their study (n = 1416) that MMS conserved function in digital melanoma by avoiding amputation and was associated with a low local recurrence rate of 0.14%.…”
Section: Mohs Micrographic Surgery For Different Types Of Skin Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…4 Furthermore, the addition of immunohistochemical stains such as MART-1, MEL-5, and SOX-10 may facilitate the accurate interpretation of frozen sections in MMS for LM and thin HNM and even rival the accuracy of conventional histology while permitting peripheral margin control. [2][3][4]11,18,33,[39][40][41] Although the 2012 Appropriate Use Criteria has included the implementation of MMS for MIS, the technique is still underused despite the potential advantages. 7,42 For instance, based on Medicare data until 2013, only 0.3%-3.5% of Mohs cases in the United States were performed on melanomas, 38,43,44 and rates of utilization of Mohs for MIS do not seem to have increased.…”
mentioning
confidence: 99%